1992
DOI: 10.3109/00016359209012744
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parkinson's disease on oral health

Abstract: Thirty patients with Parkinson's disease were investigated with regard to their oral health. They had significantly more teeth and less caries than a control group of corresponding age. However, the salivary secretion rate was significantly lower with advancing parkinsonian symptoms. It is concluded that not only motor impairment but also autonomic dysfunction, as an expression of a more advanced neuron degeneration, could be of importance when the possibility of maintaining a good oral health in parkinsonian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
5
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 9 publications
2
74
5
6
Order By: Relevance
“…18 Second, PD patients may be suffering from mastication disorders with oral dyskinegia 7,19 or xerostomia 20 caused by the administration of anticholinergics and so on. In contrast, Persson et al 12 failed to show a significant difference in the rate of those with chewing difficulties between PD patients and a control population sample because of the small sample size (10 of 30 PD patients [33%] complained of chewing difficulties, as did 20 of 526 controls [4%]).…”
Section: Methods Of Surveymentioning
confidence: 96%
See 2 more Smart Citations
“…18 Second, PD patients may be suffering from mastication disorders with oral dyskinegia 7,19 or xerostomia 20 caused by the administration of anticholinergics and so on. In contrast, Persson et al 12 failed to show a significant difference in the rate of those with chewing difficulties between PD patients and a control population sample because of the small sample size (10 of 30 PD patients [33%] complained of chewing difficulties, as did 20 of 526 controls [4%]).…”
Section: Methods Of Surveymentioning
confidence: 96%
“…This result was the opposite of the results of studies reported in Europe showing that caries were generally less common in PD patients than in controls, and that teeth were retained longer in PD patients than in controls. 12,18 This may be explained by the following possibilities. Many PD patients in the present survey had lost their teeth due to many years of poor oral hygiene because fewer PD patients brushed their teeth every day or they had difficulty going to a dental clinic in the early stage of caries.…”
Section: Methods Of Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinsonlu hastaların aynı yaş aralığındaki kontrol grubuna göre daha az diş kaybı ve çürük insidansı gösterdiğini rapor etmişlerdir. 41 Fukayo ve arkadaşları da kontrol grubuna göre daha az çürük diş ve ilgili değişikliler bulmuşlardır. 16 Parkinsonlu hastalarda motor ve kognitif bozulmalarla ilişkilendirilen diş çürükleri sık görülen komplikasyonlar arasındadır.…”
Section: Siyalore Ve Salya Akışıunclassified
“…alginate in the conventional manner using a stock tray and the primary cast was obtained (Figure 1). Anterior teeth (11,21) was selected based on patient's facial form (SR Vivadent from Ivoclar). An appropriate shade was chosen matching the adjacent teeth (A2 using Ivoclar vivadent shade guide).…”
Section: Case Reportmentioning
confidence: 99%